2017
DOI: 10.3389/fmicb.2016.02172
|View full text |Cite
|
Sign up to set email alerts
|

Lethal Experimental Tick-Borne Encephalitis Infection: Influence of Two Strains with Similar Virulence on the Immune Response

Abstract: Tick-borne encephalitis virus (TBEV) is a tick-transmitted arbovirus that causes serious diseases in humans in Europe and Northern Asia. About 6000–10,000 cases are registered annually, and one-third of them lead to sequela with different degrees of severity. Two TBEV strains (Absettarov and EK-328) similar in virulence rate in laboratory mice were used to study pathogenesis and immune response upon lethal infection in mice. The strains differed in the dynamics of appearance of virus, IFNs and other cytokines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…TBEV strains (Table 1 ) were described previously (Gritsun et al, 1997 ; Romanova et al, 2007 ; Zlobin et al, 2007 ; Kozlovskaya et al, 2010 ; Vorovitch et al, 2015 ; Chernokhaeva et al, 2016b ; Shevtsova et al, 2016 ). The viruses were stored at −70°C as a 10% mouse brain suspension or a culture supernate (CS) of infected PEK cells.…”
Section: Methodsmentioning
confidence: 99%
“…TBEV strains (Table 1 ) were described previously (Gritsun et al, 1997 ; Romanova et al, 2007 ; Zlobin et al, 2007 ; Kozlovskaya et al, 2010 ; Vorovitch et al, 2015 ; Chernokhaeva et al, 2016b ; Shevtsova et al, 2016 ). The viruses were stored at −70°C as a 10% mouse brain suspension or a culture supernate (CS) of infected PEK cells.…”
Section: Methodsmentioning
confidence: 99%
“…We also assessed several virus-related factors that could lead to TBE breakthrough infections. The differences in the vaccine efficacy against various TBEV strains can be explained by several reasons, including high virulence of a particular strain [70], features of the interaction of different strains with the immune system [39], and genetic [71,72] or structural heterogeneity of the virus sample. It was previously shown that the vaccine efficacy can be associated with the properties of the virulent virus and, probably, with its antigenic structure [59].…”
Section: Discussionmentioning
confidence: 99%
“…Such factors as the infection dose of the virus, its virulence, reproduction rate, route of inoculation, etc. were shown to influence the severity of the disease and the immune response [39].…”
Section: Introductionmentioning
confidence: 99%
“…As a critical kinase involved in innate immunity, the activity of TBK1 is tightly regulated to maintain immune homeostasis. K63-linked polyubiquitination of TBK1 at Lys30 and Lys401 and autophosphorylation of TBK1 at Ser172 were shown to be critical for its activation (Wang et al, 2009 ; Li et al, 2011 ; Ma et al, 2012 ; Tu et al, 2013 ; Shevtsova et al, 2016 ). Modification of TBK1 at Lys694 by the small ubiquitin-like modifier SUMO contributes to the ability of TBK1 to bind to adaptors for the transduction of IFN signaling (Saul et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%